State of Exception, Law and Economy: A socio-legal approach to the economy of exception in an era of crisis - Jose Manuel Atiles-Osoria; David Whyte (Oñati Socio-Legal Series)
Departing from a critical understanding of the relationship between state, law and power, we propose a critical overview of the concept of the state of exception developed by Giorgio Agamben. We emphasise the idea that the principle of legal exceptionality is not as merely used in response to the current crisis in capitalism, but is an enduring and core technique of power used by states to reproduce economic and colonial power relations. Thus, this paper offers three core points of departure from dominant understandings of the state of exception. First, we urge a rupture of the crude opposition between positive law and the state of exception. Second, we argue for a rejection of limited Western concept of (liberal, political) rights. Finally, we argue for an attention to the materiality of power relations, rather than a narrow focus on the power projected by formal institutions of state power.